ENTREPRENEURSHIP COMPETENCE IMPROVEMENT PROGRAM STRATEGIES FOR MICRO ENTERPRISES AND SMALL IN BOGOR DISTRICT - Warcito Warcito; Hamidah Hamidah; Corry Yohanna (Indonesian Naval Technology College STTAL, 2021)
Educated human resources who gain knowledge and work experience are expected to increase their dexterity, skills and abilities in working so that they are able to produce extraordinary performance which ultimately brings higher economic value. For the Bogor Regency government, educated and trained human resources can reduce the unemployment rate and can also increase the number of labor force participation which has a direct impact on increasing worker wages and labor productivity which in turn has an impact on a positive trend of economic growth. The increase in labor productivity in addition to making a positive contribution can also affect income inequality. The Bogor Regency Government has an obligation to create job opportunities for educated and trained Human Resources as well as Human Resources who are not educated and trained. The increasing number of unemployed occurs due to the increase in the number of job seekers while there are insufficient job opportunities. Human Resource Development is closely related to the development of Micro, Small and Medium Enterprises. Micro, Small and Medium Enterprises make up the majority of businesses worldwide and are important contributors to job creation and global economic development. The number of unemployed is currently more dominated by graduates of Senior High School/Vocational and Higher Education (educated workforce). Human Resource Development is closely related to the development of Micro, Small and Medium Enterprises. Micro, Small and Medium Enterprises make up the majority of businesses worldwide and are important contributors to job creation and global economic development. Keywords: Human Resources, labor productivity, Micro, Small and Medium Enterprises and SWOT.